Geo-economic Factors of an Intensification Development of Laos in Association of Southeast Asian Nation Conditions - Shkvarya, Lyudmila V.; Strygin, Andrey V.; Rusakovich, Vasilij I. (International Review of Management and Marketing, 2016)
In ASEAN since 2015 came into force the creation of the project “ASEAN Economic Community”. In this regard, it is important to examine the consequences of this process, particularly with regard to individual countries, in particular – the least developed, which include Laos. Laos is a member of ASEAN, is also directly involved in the process of formal and actual regional economic integration and the formation of the ASEAN Economic Community. In the XXI century the world economy undergoes a significant transformation, increased global instability. Among them – the deepening of regional economic integration processes in different regions of the world – in Western Europe (EU), North America (NAFTA), the South-East Asian Nations (ASEAN). The ASEAN countries occupy a strategic location on the route from the Indian Ocean to the Pacific, being at the crossroads connecting the Pacific basin to the Middle East, Africa and Europe. Keywords: ASEAN, Laos, regional economic integration, ASEAN Economic Community JEL Classifications: O53, O50, F02